THE IMPACT OF STRATEGIC LEADERSHIP IN TO ACHIEVE ORGANIZATIONAL PROSPERITY IN TOURISM ORGANIZATIONS: AN EXPLORATORY STUDY OF OPINIONS OF A SAMPLE OF MANAGERS IN THE IRAQI TOURISM AUTHORITY - Prof. Dr. Dina Hamid Jamal (Scholars Digest Publishing, 2024)
The Research Aims to Clarify Role of Strategic Leadership (SL) Organizational Prosperity Enhancing (OP) In Iraqi Tourism Authority (ITA) By Studying the Dimensions of Strategic Leadership Represented In (Strategic Direction (SD), Development Human Capital (DHC), Ethical Practices (EP), Core Capabilities (Cc). In Addition To, Dimensions Of (OP), Which Are (Creativity, Intellectual Capital (CI), And Infrastructure). Problem Arises in Knowing Extent to Which (SL) Uses Organizational Prosperity Techniques. SO, The Study Was Conducted In (ITA), A Questionnaire Was Distributed. The Study Concluded That There Are Correlations and Influences For (SL)In Use Of (OP)Techniques.
Keywords: strategic leadership - organizational prosperity.